Economics of the Indus River Sands - Tahirkheli, Dr. R. A. Khan (Journal of Himalayan Earth Sciences, 1965)
The Indus River has for centuries attached the attention of the prospectors and geologists because of gold in its alluvials. The goldwashers are still working along the Indus River banks, using primitive methods to extract gold by washing sand and gravel. Recent studies conducted by the author show that an experienced goldwasher extracts about 1.05 grains of gold per cubic yard. The high value minerals left in gold tailings are scheelite, uraninite, and cassiterite. An attempt has been made in this paper to evaluate their proportions in the heavy fraction and bulk sands to see whether they can be won economically as co–products of gold.